2011
DOI: 10.1007/s10499-011-9463-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated ambient histamine level on survival, growth, sexual maturity and tissue histamine accumulation of the mysis Neomysis awatschensis and Neomysis japonica Nakazawa

Abstract: In Asia, trash fish have been routinely used in aquaculture often due to their local availability and lower costs compared to formulated feed. However, stale trash fish contain high levels of biogenic amines, which have been reported to be harmful to poultry and some aquatic animals. The present study elevated the effects of histamine levels in the water on survival, growth, sexual maturity and tissue histamine accumulation of two estuarine mysis, Neomysis awatschensis and Neomysis japonica Nakazawa. Newly hat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Work from Morimoto et al (2001) suggested that brain histamine involves in modulating mouse feeding behavior. Yang and colleagues (Yang et al, 2012) showed that exogenous histamine had an effect on tissue histamine accumulation and also reduced body length, body weight and development time in the crustacean Neomysis japonica Nakazawa. Although the effect of histamine on feeding behavior and growth/development in insects has not been studied, it is possible that thermally driven increases in histamine reduces food intake in mayfly larvae, resulting in smaller body size and associated reduction in fecundity (Figure 4).…”
mentioning
confidence: 99%
“…Work from Morimoto et al (2001) suggested that brain histamine involves in modulating mouse feeding behavior. Yang and colleagues (Yang et al, 2012) showed that exogenous histamine had an effect on tissue histamine accumulation and also reduced body length, body weight and development time in the crustacean Neomysis japonica Nakazawa. Although the effect of histamine on feeding behavior and growth/development in insects has not been studied, it is possible that thermally driven increases in histamine reduces food intake in mayfly larvae, resulting in smaller body size and associated reduction in fecundity (Figure 4).…”
mentioning
confidence: 99%
“…As a toxic dietary component, histamine has attracted much attention from aquatic animal nutritionists in recent years. Previous studies have shown that dietary histamine significantly decreased the growth performance of the juvenile group ( Epinephelus coioides ) [ 35 ], mysis ( Neomysis japonica Nakazawa ) [ 36 , 37 ], American eels ( Anguilla rostrata ) [ 38 , 39 ], yellow catfish ( Pelteobagrus fulvidraco ) [ 29 ], and rainbow trout ( Oncorhynchus mykiss ) [ 40 ]. In this study, our data exhibited that dietary histamine below 60 mg/kg has limited effects on the growth of striped catfish, whereas dietary histamine above 120 mg/kg significantly decreased the growth, suggesting that the growth-inhibiting effect of dietary histamine was dose-dependent.…”
Section: Discussionmentioning
confidence: 99%